Growth response of common carp, Cyprinus carpio (L.) to aquatic weed incorporated diets - Somasekhar, D S; Venkateshwarlu, M; Shanmugam, M; Rangaswamy, B L (Indian Journal of Fisheries, 2011)
Experiments were conducted to find out the comparative usefulness of floating aquatic weeds incorporated feed for carp fry. Pistia straiotes and Lemna major as major ingredients and dried silkworm pupae powder as minor ingredient were used and growth was compared with conventional feed i.e. rice bran and ground nut oil cake in the ratio of 1:1. Experiments were conducted for 28 days period. The average growth of carp fry grown on Pistia leaf based feed (PF) was marginally superior to that obtained with LF (Lemna based feed) and CF (conventional feed).